2009
DOI: 10.1021/jp810653z
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions and Structures of Novel Pyrenes Potentially Useful in Photovoltaic Applications

Abstract: A series of conjugated compounds, 6,7,15,16-tetrakis(alkylthio)quinoxalino[2',3':9,10]phenanthro[4,5-abc]phenazine (TQPP-[SC(n)](4)) (n = 6, 8, 10, and 12), which display p-channel characteristics was synthesized. These materials show promise for use in liquid crystalline photovoltaic applications. To determine their applicability, the different phase structures and transitions of these compounds were studied with differential scanning calorimetry (DSC), polarized light microscopy (PLM), wide-angle X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…From the POM analysis, it is found that the transition at elevated temperature is associated with liquid crystal (LC)-isotropic melt (I) transition of the SiLC. 14 The fast cooled SiLC reveals a glassy LC phase below T g ¼ 22 C.…”
Section: Thermodynamic Phase Transitions and Their Corresponding Stru...mentioning
confidence: 93%
“…From the POM analysis, it is found that the transition at elevated temperature is associated with liquid crystal (LC)-isotropic melt (I) transition of the SiLC. 14 The fast cooled SiLC reveals a glassy LC phase below T g ¼ 22 C.…”
Section: Thermodynamic Phase Transitions and Their Corresponding Stru...mentioning
confidence: 93%
“…The effects of bulky substituents and branched alkyl tails on the modification of phase structures and molecular packing have been nicely illustrated by previous studies. 42,43 Polyhedral oligosilsesquioxanes (POSSs), regarded as small inorganic nanoparticles with diameters up to 1.5 nm, 44 were chosen as the bulky group because of their well-defined nature. The incorporation of POSS into organic molecules can bring remarkable improvement in the thermal and oxidative stability.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…This metastable phase melts, in the subsequent heating, at 152 C with an identical heat of transition, revealing that the metastable phase is a liquid crystal-like phase for which the transition usually does not exhibit supercooling in transition temperature. 14,17 Formation of the stable phase requires long thermal annealing, such as annealing the metastable phase at 145 C for 3 days.…”
Section: Phase Behaviors Of Dizncpdmentioning
confidence: 99%
“…[1][2][3][4] Combining p-type and n-type p-conjugated molecules enables the photo-induced charge generation process and provide functions in applications such as photovoltaics and artificial photosynthesis. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In particular, using self-assembly to construct supramolecular structures of these p-conjugated molecules has been recognized as an important approach to generate ''supramolecular electronics''. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Research using [60]fullerene (C 60 ) as an electron acceptor (A) and porphyrin as an electron donor (D) has been extensively carried out.…”
Section: Introductionmentioning
confidence: 99%